A Analisis Pendapatan Rumah Tangga Usaha Pertanian di Provinsi Sumatera Barat - Diana, Rita (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.2, Agustus 2019 (pp. 111-247)DO - 10.24843/JKET.2019.v12.i02.p02, 2019)
This study aims to determine the determinants of the variation in household income that seeks in the agricultural sector. The statistical method used to examine it is Log-logistic regression model of three parameters with estimation method using Bayesian method. Based on the model, it can be seen that the characteristics of household of agricultural business (RTUP) of West Sumatera which have positive correlation to household income are percentage of productive age farmer, percentage of farmers who are educated above junior high, percentage of male farmer, area of ??residence, land use, sources of financing, grants, saprodi access, counseling, farmer groups, cooperative utilization and marketing of agricultural products. Among all these factors, which contributed the most in increasing the income of the RTUP in West Sumatera were the percentage of productive farmers, the area where the farmer lived, the provision of access to saprodi and the utilization of the cooperative.